2007
DOI: 10.1007/s00779-007-0177-9
|View full text |Cite
|
Sign up to set email alerts
|

Informing augmented memory system design through autobiographical memory theory

Abstract: Autobiographical memory (AM) is the ''memory for the events in one's life'' [1]. Often it is assumed that in order to remember all those events, you just need to record everything and when you replay these recordings you will remember those events. You can compare this with a library metaphor that has been used to explain AM according to the record-keeping approach. However, after many years of AM-research it was concluded that AM is stored in a different manner, namely according to the constructionist approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(40 citation statements)
references
References 29 publications
(23 reference statements)
1
38
0
1
Order By: Relevance
“…People best remember specific aspects of autobiographical events, including who was involved and what happened, whereas when or where events occurred is less well recalled (Linton, 1986, Wagenaar, 1986. Underlying conceptions of autobiographical memory have also shifted from traditional views of a knowledge base (Conway and Pleydell-Pearce, 2000), to instead proposing core roles for reconstruction and social dynamics (Crabtree et al, 2004Fivush and Nelson, 2004, Leichtman, and Wang, 2005, van den Hoven, 2004. For example, Cohen (1989) describes how sharing autobiographical memories serves as a mechanism for self-disclosure, developing or deepening social bonds.…”
Section: Autobiographical Memorymentioning
confidence: 99%
See 2 more Smart Citations
“…People best remember specific aspects of autobiographical events, including who was involved and what happened, whereas when or where events occurred is less well recalled (Linton, 1986, Wagenaar, 1986. Underlying conceptions of autobiographical memory have also shifted from traditional views of a knowledge base (Conway and Pleydell-Pearce, 2000), to instead proposing core roles for reconstruction and social dynamics (Crabtree et al, 2004Fivush and Nelson, 2004, Leichtman, and Wang, 2005, van den Hoven, 2004. For example, Cohen (1989) describes how sharing autobiographical memories serves as a mechanism for self-disclosure, developing or deepening social bonds.…”
Section: Autobiographical Memorymentioning
confidence: 99%
“…Souvenirs and recollection were also investigated by van den Hoven (2004). Analysis of focus group discussions suggested that souvenirs are esoteric: carrying meaning for owners that is obscure to others.…”
Section: Technology For Personal Recollectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have demonstrated the effectiveness of memory-association tasks in justification of the symbolic meanings for archetypal contents [23,24]. This is also in accord with the mainstream of research into memories: the constructionist approach of memory recollection [25]. This approach regards memories as dynamic recollections instead of static records of something.…”
Section: Implication For Researchmentioning
confidence: 53%
“…Esta memória é muito organizada, construída ao longo de toda a vida, com tendência a preservar o essencial de cada evento e possui diferentes conteúdos, contexto espacial e temporal, emocional e narrativo (Aurélio & Cláudio, 2009;Nelson, 1993;Robinson, 1986;Rubin, 2005;Williams et al, 2007). A memória de um acontecimento não é uma cópia da realidade, o que implica que possa, ao longo do tempo, ser modificada, distorcida ou reconstruída (Aurélio & Cláudio, 2009;Rubin, 1986;van den Hoven & Eggen, 2008). Nesta linha, para Conway e Pleydell-Pearce (2000) "(…) as memórias autobiográficas são construções mentais dinâmicas transitórias geradas a partir de uma base de conhecimento subjacente" (p.…”
Section: Memórias Autobiográficasunclassified